2019
DOI: 10.1007/s40800-019-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s Gangrene in a Patient with Type 2 Diabetes Mellitus Treated with Empagliflozin: A Case Report

Abstract: Sodium-glucose cotransporter-2 (SGLT2) inhibitors have been reported as possibly associated with Fournier’s gangrene (FG). This case report describes a 34-year-old Japanese man who was diagnosed with FG after the administration of empagliflozin for type 2 diabetes mellitus (T2DM). He presented with pain and swelling in the perineum and groin 142 days after initiating empagliflozin. The clinical features, laboratory data, and computed tomographic findings were consistent with FG. Surgical drainage and debrideme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Kumar et al [9] reported a 41-year-old male patient with T2DM with an HbA1c of 11.2% using empagliflozin, and Onder et al [10] reported a 64-year-old male patient with T2DM with an HbA1c of 7.4% using dapagliflozin. However, similar to our case, Nagano et al [11] reported a 34-year-old male patient with T2DM with an HbA1c of 6.5% at the time of FG onset who was on sitagliptin, glibenclamide, and empagliflozin therapy. The patient had no additional complications from DM besides FG [11].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Kumar et al [9] reported a 41-year-old male patient with T2DM with an HbA1c of 11.2% using empagliflozin, and Onder et al [10] reported a 64-year-old male patient with T2DM with an HbA1c of 7.4% using dapagliflozin. However, similar to our case, Nagano et al [11] reported a 34-year-old male patient with T2DM with an HbA1c of 6.5% at the time of FG onset who was on sitagliptin, glibenclamide, and empagliflozin therapy. The patient had no additional complications from DM besides FG [11].…”
Section: Discussionsupporting
confidence: 86%
“…However, similar to our case, Nagano et al [11] reported a 34-year-old male patient with T2DM with an HbA1c of 6.5% at the time of FG onset who was on sitagliptin, glibenclamide, and empagliflozin therapy. The patient had no additional complications from DM besides FG [11]. Thus, the risk for developing FG remains in spite of good glycemic management with SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the late stage presentation and the limited resources, the management of this case was successful, although it required a long-time admission and it absorbed limited human and economic resources. This is not the first case reported as others have been documented in recent years, especially in industrialised countries [10][11][12][13]. However, we present here the first systematic review on this topic.…”
Section: Discussionmentioning
confidence: 52%